Seismic response of a typical 3-legged jacket of fixed offshore platform in Malaysia due to Philippines earthquake - Solihah, A. Aziz (2015)
The offshore structural design practice in Malaysia only focus more on wind and wave effects analysis rather than seismic effect. At the east of Malaysia, the Philippine plate moves westward with an estimate velocity of 80mm/year and cause micro faults in Sabah. Thus, this thesis develops the earthquake ground motion due to Philippine earthquake for assessment of offshore platform in Malaysia. Besides, the adequacy of existing design of offshore platform in Malaysia is determined when subjected to earthquake loading. The analysis of behavior of the offshore platform structures of 3-legged fixed offshore structures under the earthquake effect is obtained to develop the earthquake design criteria for the offshore structures that are located in Malaysia region. The assessment of fixed offshore structure also covers the static and dynamic for the earthquake analysis by using the code of practice of “Recommended Practice for Planning, Designing and Constructing Fixed Offshore Platforms (API RP-2A, 2000). As for designing the offshore platform, this analysis is considering the dead load, live load, environmental loads (wind, wave and current load) and earthquake load such that free vibration, time history and response spectrum. The SAP 2000 computer program has been used to check the steel structure based on Eurocode 3, 2005. The most critical member of jacket offshore platform for the analysis of the various load also determined by compared the element capacity with manual calculation. However, there are assumption has been made such that the structure is fixed to the ground and the geometry, material properties and section properties of the structure are represent almost the same from the actual structure